PKM2 Interacts With the Cdk1-CyclinB Complex to Facilitate Cell Cycle Progression in Gliomas - Shigeo Ohba; Shigeo Ohba; Yongjian Tang; Yongjian Tang; Tor-Christian Aase Johannessen; Tor-Christian Aase Johannessen; Joydeep Mukherjee (Frontiers in Oncology, 2022)
PKM2 is a phosphotyrosine-binding glycolytic enzyme upregulated in many cancers, including glioma, and contributes to tumor growth by regulating cell cycle progression. We noted, however, that in multiple glioma cell lines, PKM2 knock-down resulted in an accumulation of cells in G2-M phase. Moreover, PKM2 knock-down decreased Cdk1 activity while introducing a constitutively active Cdk1 reversed the effects of PKM2 knock-down on cell cycle progression. The means by which PKM2 increases Cdk1 activity have not been described. Transient interaction of T14/Y15-phosphorylated Cdk1 with cyclin B allows Cdk7-mediated pT161 Cdk1 phosphorylation followed by cdc25C-mediated removal of pT14/Y15 and activation of Cdk1 in cycling cells. In the present course of investigation, PKM2 modulation did not influence Cdk7 activity, but phosphotyrosine binding forms of PKM2 co-immunoprecipitated with pY15-containing Cdk1-cyclinB and enhanced formation of active pT161 Cdk1-cyclin B complexes. Moreover, exogenous expression of phosphotyrosine binding forms of PKM2 reversed the effects of PKM2 knock-down on G2-M arrest. We here show that PKM2 binds and stabilize otherwise transient pY15-containing Cdk1-cyclinB complexes that in turn facilitate Cdk1-cyclin B activation and entry of cells into mitosis. These results, therefore, establish metabolic enzyme PKM2 as a direct interactor and activator of Cdk1-cyclin B complex and thereby directly controls mitotic progression and the growth of brain tumor cells.